Effect of polymeric films on physiological, biochemical and enzymatic changes in eggplant (Solanum melongena) under ambient conditions - SIDHU, MOHINDER KAUR; MAHAJAN, B V C; TANDON, RITU; DHATT, AJMER SINGH; DHILLON, WASAKHA SINGH (The Indian Journal of Agricultural Sciences, 2017)
Brinjal (Solanum melongena L.) fruits were harvested at physiological maturity stage and packed in polymeric films, viz heat shrinkable film (15μ) and cling film (15μ). The film packed and unpacked (control) fruit were stored under ambient conditions. Both films proved quiet effective in improving the post harvest life and maintaining the quality of fruits for 6 days. Shrink and cling film created modified atmosphere around the produce and reduced physiological loss in weight (0.24 and 3.67%, respectively), shrinkage and maintained firmness (12.92 and 10.92 lb, respectively) and colour (L-23.32 and 24.59, respectively) of the fruit until 6th day of storage. Ascorbic acid (12.08 and 11.25 mg/100g, respectively) and anthocyanin content (2.50 and 1.77 mg/100g, respectively) of the fruit was better maintained in packed fruits as compared to control. Total phenols remained higher in packed fruits (52 and 48 ppm, respectively). PPO activity displayed slighter and sluggish increase as well as decrease in the packing treatments that was prompt in case of unpacked fruits and reached to the maximum level (60.63 units/100 mg) on 6th day of the storage. Thus, packaging technology helps in minimizing the postharvest losses and maintaining the quality and nutritional value of brinjal during storage under ambient conditions.